AUTISM SYNDROME - Toshtemirova Rozahon Avazbek qizi (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, we will discuss the most common autism in children. This mysterious disease is currently being studied by scientists. A child with autism looks around differently. It is estimated that one in every 88 children in the world has autism. Such children are not different from others in appearance, only they think differently. Here’s a few basic facts about a stomp pad and how it is used to treat children with autism.